Actualization of strategies for beef quality control in south western Nigeria (2005)
A major private abattoir wd meat processing plant in south-westem Nigeria was studied in this article to determine its compliance with control over dissemination of parasitic and microbial diseases from beef to man. To ensure total quality control, a private veterinarian sourced for cattle on farms and supplied these to the abattoir. In addition, a public health veterinarian in government service at the abattoir carried out antemortem tests, postmortem inspection and removal of unwholesome cattle. Diseases such as fascioliasis, tuberculosis, cysticercosis and brucellosis were effectively controlled in this way. Hence, United African Company (UAC) Foods provides wholesome beef to the community